Peningkatan Kemampuan Representasi Matematis dan Self Confidence Siswa Melalui Pembelajaran Humanistik Berbasis Pendidikan Matematik Realistik - Lia Rista; Cut Yuniza Eviyanti; Siti Hadijah (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2019)
Abstract The objectives of this study are: (1) to find out the difference of improvement of students’ mathematical representation ability and students’ self-confidence through humanistic learning based on realistic mathematical approaches and conventional learning reviewed (a) as a whole and (b) at the student level (high, medium, low), (2) to find out is there interaction between learning process and students’ initial ability on the improvement of students’ mathematical representation ability and students’ self-confidence. The population of this study is all of the student in SMA Negeri 1 Lhokseumawe. The sample of this study was taken randomly consist of two classes . The two way ANAVA was used to analyzed the data of this study. The results of this study indicate that the increasement of students’ mathematical representation who learned with humanistic learning based on PMR is higher than the students’ who learned with conventional learning.The Increasement of students’ self-confidence who learned with humanistic learning based on PMR is higher than the students who learned with conventional learning. There is interaction between learning model (problem-based learning and conventional learning) and students’ initial mathematical ability toward the increasement of students' mathematical representation ability. There is interaction between learning model (problem based learning and conventional learning) and students’ initial mathematical ability toward the increasement of students’ self-confidence. Keywords:humanistic learning based on PMR, Conventional Learning, Mathematical Representation, and Self-Confidence. Abstrak Penelitian ini bertujuan: (1) Untuk mengetahui perbedaan peningkatan kemampuan representasi matematis dan self confidence siswa melalui pembelajaran humanistik berbasis pendidikan matematika realistik (PMR) dan pembelajaran biasa (PB) ditinjau dari:(a) secara keseluruhan, (b) berdasarkan level siswa (tinggi, sedang, rendah), (2) Untuk mengetahui Apakah terdapat interaksi antara strategi pembelajaran dengan level siswa terhadap kemampuan representasi matematis dan self confidence siswa. Populasi penelitian adalah seluruh siswa SMA Negeri 1 Lhokseumawe. Sampel penelitian diambil secara acak sebanyak 2 kelas. Analisis data dilakukan dengan ANAVA Dua Jalur. Hasil penelitian ini menunjukkan bahwa Peningkatan kemampuan representasi matematis siswa yang diberi pembelajaran humanistik berbasis PMR lebih tinggi daripada siswa yang diberi PB. Peningkatan self confidence siswa yang diberi pembelajaran humanistik berbasis PMR lebih tinggi daripada siswa yang diberi PB. Terdapat interaksi antara model pembelajaran dan KAM terhadap peningkatan kemampuan representasi matematis siswa. Terdapat interaksi antara model pembelajaran dan KAM terhadap peningkatan self confidence siswa. Kata Kunci: Pembelajaran Humanistik berbasis PMR, Pembelajaran Biasa, Representasi Matematis, dan Self Confidence.